Simulation and Experimental Study on Splash Lubrication Flow Field in Gearbox of EMU - Kaiwen Lu; Juan Zhao; Chuanyang Wang; Yijie Huo; Qiumei Zheng; Jie Sun (Jixie chuandong)
Splash lubrication is the most important lubrication method in gearbox of EMU at present，it is of great significance to study the law of flow field distribution for gear box lubrication. A simulation test platform for splashing lubrication flow field of gearbox is established after simplifying the gearbox of EMU，and splash lubrication capture test is carried out. Based on the theoretical knowledge of computational fluid mechanics，a three-dimensional numerical analysis model of the flow field simulation test platform is established by using PumpLinx software. The reliability of the three-dimensional numerical analysis model is verified by the comparison between the test and the simulation. Finally，the simulation and prediction of the flow field of the lubricating oil in the gearbox of a EMU during going up，down and turning are realized.